2014
DOI: 10.4049/jimmunol.1302241
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Regulate Peripheral B Cell Numbers in Both Mice and Humans

Abstract: The view of eosinophils (Eos) as solely effector cells involved in host parasite defense and in the pathophysiology of allergic diseases has been challenged in recent years. In fact, there is a growing realization that these cells interact with other components of innate and adaptive immunity. For example, mouse Eos were recently demonstrated to promote plasma cell retention in the bone marrow. However, it remains unknown whether Eos influence the biology of normal B lymphocytes. In this study, we specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 60 publications
4
51
0
Order By: Relevance
“…Eosinophils have been demonstrated to be required for long-term maintenance of plasma cells in the bone marrow (41, 42). We tested whether eosinophils influence numbers of plasma cells or the quantity and qualities of antibodies produced during T. spiralis infection.…”
Section: Resultsmentioning
confidence: 99%
“…Eosinophils have been demonstrated to be required for long-term maintenance of plasma cells in the bone marrow (41, 42). We tested whether eosinophils influence numbers of plasma cells or the quantity and qualities of antibodies produced during T. spiralis infection.…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvant-elicited eosinophils express IL-4, IL-6, IL-10, TNF and the plasma cell survival factor APRIL 128 and are required for early alum-induced activation of B cells and the production of antigen-specific IgM 127 . In both mice and humans, eosinophils also support increased numbers of peripheral B cells 129 ; and in mice, eosinophils promote B cell survival, proliferation and immunoglobulin secretion by a contact-independent mechanism 129 .…”
Section: Steady-state Functions Of Tissue Eosinophilsmentioning
confidence: 99%
“…Using adoptive transfer protocols in eosinophil-ablated recipient mice, it was shown that plasma cell survival is further enhanced when eosinophils are first activated with adjuvant [60], consistent with a role for eosinophils in bone marrow plasma cell survival during infection. Eosinophils are also capable of regulating peripheral B cell homeostasis and proliferation in mice [61]. Although eosinophils are dispensable for the parasite-specific IgM response during primary infection by Strongyloides stercoralis [62], they are required for production of specific IgG2c in Trichinella infection [45].…”
Section: Secondary Infection: Confirming the Dogma In Vivomentioning
confidence: 99%